“De modernes særlige problem”: Dramatiske helte og prosaisk verden i Goethes Wilhelm Meisters læreår - Eriksson, Birgit (Passage - Tidsskrift for litteratur og kritik, 2025)
"The Specific Problem of the Moderns": Dramatic Heroes and Prosaic Worlds in Wilhelm Meister’s Apprenticeship The article studies the role of theatre and specifically Hamlet in Goethe’s Wilhelm Meister’s Apprenticeship (1795-96). Comparing the canonized interpretation of Hamlet to the novel’s own form, and relating it to developments in German theatre, literature and philosophy, the article argues that Goethe’s novel, by including Hamlet, offers important perspectives on the characteristics and importance of the modern novel in a radically changing world.